The Mapping and Characterization of Product and Recreation Ecosystem Services in the Nahuelbuta Mountain Range - Arriagada, Kimberly; Aguayo Arias, Mauricio (Investigaciones Geográficas, 2018)
Ecosystem services are the benefits that people derive from natural ecosystems. The characterization and quantification of ecosystem services contribute to the sustainable management of natural resources. Forests are ecosystems that provide multiple services, including non-timber forest product provision services and cultural recreation services. In this context, the study focused on the analysis and evaluation of the ecosystem services of the Cordillera de Nahuelbuta through the mapping and quantification of these services. We analyzed how the degree of naturalness of forest formations influences the generation of these services. The stock of non-timber forest products was estimated by concentrating on fruits, seeds and fungi. The results show that the area harbors up to 36 species that provide non-timber forest products in the forested areas of the temperate mixed forest of Nahuelbuta of Nothofagus dombeyi and N. obliqua and the coastal temperate laurifolius of Aextoxicon punctatum and Laurelia sempervirens. In relation to the recreation service, there was a high potential for recreation and ecotourism in the area, especially the sectors of Caramávida, Trongol and Nahuelbuta National Park which present an appropiate combination of attributes for recreation such as singular resources, scenic beauty, accessibility and tourism attractiveness. The results reveal the need for an urgent and adequate protection of those core areas where the largest provision of the analyzed ecosystem services is concentrated.